COVID-19 HANDLING IN THE BORDER AREAS OF INDONESIA - Endah Rantau Itasari (Universitas Pendidikan Ganesha, 2020)
Indonesia is a country that has contracted Coronavirus Disease 2019. The status of an archipelago and borders with ten countries at sea and three countries on land borders makes Indonesia must be extra hard to become its border region so that other citizens do not carry the virus transmission through the borders of Indonesia. Preventing management at the National Entrance (Airport, Port and PLBDN) in anticipation of COVID-19 includes the following aspects: Early detection of suspected travel perpetrators; Interview and anamnesis of the sick Traveler to ascertain the possibility of COVID-19 symptoms in the examination room; Reporting cases of Travel Actors suspected of contracting COVID-19 to PHEOC; Refer for isolation of Travel Actors suspected of contracting COVID-19 to the referral hospital using ambulances that match the criteria; Health quarantine in transports and items suspected of being exposed to COVID-19.